THE COMPARATIVE ANALYSIS OF IFRS ADOPTION THROUGH EARNINGS RESPONSE COEFFICIENT AND CONSERVATIVE PRINCIPLE: CASE STUDY IN ASEAN COUNTRIES - Huda, Muhammad Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This purpose of this empirical study is to analyse how the market reaction and the conservative degree changes on the IFRS adoption through ASEAN member countries; Indonesia, Singapore, and Malaysia on the mining, oil, and gas industry. The study also has given others additional analysis on the profitability, leverage, and disclosures measurement towards IFRS adoption. The data collection methods used in this study reveals as observation and deep analysis to the company’s annual report, share market data, and index market data. The results of this study concluded that IFRS has given a difference on the depth analysis to the two of variance analysis; Moderated Regression Analysis and ANOVA. The result on the regression analysis shows that market response on the financial information of company’s earnings have been well-responded after IFRS adoption in ASEAN. The results on ANOVA analysis shows that even the investors reacted positively to IFRS adoption on the presented financial report, and yet most of the financial report presented by 41 companies during 2010 – 2014 not elevate the conservative degree after IFRS adoption. Furthermore, the result of additional analysis on profitability and leverage don’t changes on the post-adoption of IFRS, despite that, the company’s disclosures deliberately changes upon IFRS adoption. The conclusion has been made that IFRS adoption apparent to elevate the market trustworthy, even the value of conservative principle negative to be raised. In other words, IFRS has not already proved the relevancy and reliable information as the IASB statement in ASEAN countries. Keywords: IFRS, Earnings Response Coefficient, Conservative Principle, ASEAN